Hydrology method for environmental flows assessment of Johor River Basin under regulated and non-regulated conditions - Ab Ghani, Noor Hisham; Yusop, Zulkifli; Mat Amin, Mohd Zaki; Siaw Yin, Thian (Environmental and Toxicology Management, 2022)
This paper evaluates the capability of hydrology method for environmental flow (Eflow) assessment of Johor river basin under non-regulated and regulated conditions due to dam construction. Daily river flow data from 1971 to 2017 was used for the assessment. Generalized extreme value distribution was applied in order to estimate exceedance probabilities associated with historical observation data at different return periods. Environmental water allocations of the river at different ecological conditions were estimated using the intra-annual and inter-annual flows. This study has estimated the hydrological yearly conditions (very dry, dry, average and wet) for the river basin. Moreover, the method has also successfully proposed the environmental water allocations to achieve the desired ecological conditions, which are very good ecological (Eflow class A), good ecological (Eflow class B), medium ecological (Eflow class C), and deficient ecological conditions (Eflow class D). In general, the proposed method has been capable and acceptable for the assessment of Eflow of Johor river basin in line with sustainable water management goal.